PENANGGULANGAN PENCURIAN KENDARAAN BERMOTOR DI KABUPATEN SIDRAP - Muliyadi, Muliyadi (PETITUM, 2014)
This study aims to determine the factors that influence and how the efforts made by law enforcement officers in the handling. This research was conducted at the Institute Polres Sidrap and Sidrap correctional using data analysis techniques against one member of the interview at the police station and questionnaires Sidrap of prisoners motor vehicle theft existing Sidrap Penitentiary The findings obtained from this study showed several factors that cause motor vehicle theft: the moral factor if a person has no moral undoubtedly the person will commit an act according to the will of his own; economic factors are also very influential because of the needs that he must fulfill. The influence of environmental factors in terms of how good someone is when associating with those who often commit crimes then automatically he will imitate evil habits conducted by groups that exist in the environment, in the absence of attention to family factors in a person's family will feel marginalized and in the end he did act according to his will alone, another factor that is a factor of education, most of the main actors have a very low level of education, and law enforcement factors. The efforts made by the Indonesia Police Institution in poverty two-wheeled motor vehicle theft in Sidrap include pre-emptive efforts, preventive and repressive achieve them although, in many cases that have not been revealed as the face of various obstacles in law enforcement, but police been able to reduce the rate of motor vehicle theft quantity